2023
DOI: 10.3390/s23104937
|View full text |Cite
|
Sign up to set email alerts
|

Optical Remote Sensing in Provisioning of Ecosystem-Functions Analysis—Review

Abstract: Keeping natural ecosystems and their functions in the proper condition is necessary. One of the best contactless monitoring methods is remote sensing, especially optical remote sensing, which is used for vegetation applications. In addition to satellite data, data from ground sensors are necessary for validation or training in ecosystem-function quantification. This article focuses on the ecosystem functions associated with aboveground-biomass production and storage. The study contains an overview of the remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…This study’s results agree with other studies showing that LAI is a good predictor of AGB. For example, Vyvlečka & Pechanec, ( 2023 ), found a strong relationship between LAI and AGB in temperate deciduous forests. Similarly, Gao et al, ( 2011 ) found a strong correlation between LAI and AGB in a temperate grassland.…”
Section: Discussionmentioning
confidence: 99%
“…This study’s results agree with other studies showing that LAI is a good predictor of AGB. For example, Vyvlečka & Pechanec, ( 2023 ), found a strong relationship between LAI and AGB in temperate deciduous forests. Similarly, Gao et al, ( 2011 ) found a strong correlation between LAI and AGB in a temperate grassland.…”
Section: Discussionmentioning
confidence: 99%